Kajian Pengolahan Nilam (Patchouli) Menggunakan Metode Penyulingan Uap di Kecamatan Poleang Utara Kabupaten Bombana - dhian herdhiansyah; Subhan; La Rianda; Asriani (JURNAL AGROINDUSTRI HALAL, 2023)
This study examines the processing of patchouli oil using the steam distillation method in North Poleang District, Bombana Regency. Data collection methods: (a) observation; (b) interviews); (c) questionnaires; and (d) documentation. The method in this study is to describe the processing of patchouli oil using the steam distillation method. The results showed the processing of patchouli oil using the steam distillation method in North Poleang District, Bombana Regency. Distilleries are used with water and steam distillation systems. Distil water and steam through a kettle filled with water to the limit of the filter and patchouli leaves on the filter. Then the water is heated and produces steam passing through the material and flowing through a stainless pipe. (a) Patchouli oil is obtained from the leaves, stalks, stems and patchouli plants. Harvesting can be done 6 - 8 months after planting in plants that grow well. Nilan harvest is usually done by pruning as high as 10 - 20 cm from the ground. Production of the first leaves and twigs is still low (about 50 - 75% of normal production). Done every 4 - 6 months depending on the rainfall and soil fertility; (b) drying is usually carried out by drying, the crop (pattern leaves and stalks) are dried in the sun for 5 hours followed by wind-drying for 2 - 3 days until the moisture content reaches 12 - 15%; and (c) direct steam distillation, in which the material is in a still boiler and water vapour is drained from the boiler at the bottom of the distillate. The duration of direct steam distillation ranges from 4-6 hours.